Effect of sikkam (Bischofia javanica Blume) ethanolic extract on the quality and quantity of hyperglycemic rat sperm - Syafruddin Ilyas; Salomo Hutahaean; Rahmat S.H. Sinaga; Putri C. Situmorang (GarVal Editorial Ltda., 2022)
Context: Hyperglycemia causes diabetes mellitus (DM), abnormal metabolism, oxidative stress, and chronic complications such as impotence. Hyperglycemia causes testicular atrophy and stromal cell, seminiferous tubular damage, and spermatogenic cells. Bischofia javanica Blume is a plant that is used for the treatment of various chronic conditions and has traditionally by the people of Indonesia as a diabetes medicine. Aims: To determine the effect of B. javanica extract on the increase in the quality and quantity of sperm of hyperglycemic rats. Methods: The treatment groups consisted of; G0: negative control (-), G1: positive control (DM: alloxan induction + standard feed), G2-G4: DM + 300, 600 and 900 mg/kg BW of B. javanica leaves ethanol extract, respectively, and G5: DM + glibenclamide 0.5 mg/kg BW. Rats were dissected, and then the testes were taken to analyze sperm quantity and quality and immunohistochemistry. Results: There was a significant difference (p<0.05) in testes volume, sperm concentration and sperm motility in hyperglycemic rats. The decrease in caspase 3 expression and apoptosis was accompanied by an increase in the dose of the highest B. javanica ethanol extract, and it was seen that testicular histology in groups G4 (900 mg/kg) and G5 (glibenclamide) could improve testicular histology like in the control group (G0). Conclusions: B. javanica can improve the quality and quantity of hyperglycemic rats' sperm and also reduce apoptosis via caspase 3 in the histology of testis.